Comparison of the microwave drying kinetics of culture and natural asparagus - Kipcak, Azmi Seyhun (2018)
Asparagus (Officinalis kültür or Acutifolius natural) is an healthy food, which can be cooked or eaten raw. In this study, the microwave drying kinetics along with the color evaluation and volumetric decrease values of culture and natural asparagus are studied. For culture and natural asparagus the drying times were found as 42, 13, 10 min. and 36, 7 and 5.5 min. for at the microwave power levels of 90, 180 and 360W, respectively. Four different drying models were applied and showed that the Alibas model best fits the data. The effective moisture diffusivity values were calculated between 3.78 × 10-07 and 1.54 × 10-06 m2 s-1 for culture and 4.58 × 10-07 and 4.00 × 10-06 m2 s-1 for natural asparagus. The activation energies were found as 20.967 kW kg-1 and 146.020 kW kg-1 for culture and natural asparagus, respectively. For the color analysis, the optimal power level was found as 90 W.